Evaluation of Edge Caching/Offloading for Dynamic Content Delivery - Yuan, Chun; Chen, Yu; Zhang, Zheng (The Twelfth International World Wide Web Conference, 2003)
As dynamic content becomes increasingly dominant, it becomes an important research topic as how the edge resources such as client-side proxies, which are otherwise underutilized for such content, can be put into use. However, it is unclear what will be the best strategy and the design/deployment tradeoffs lie therein. In this paper, using one representative e-commerce benchmark, we report our experience of an extensive investigation of different offloading and caching options. Our results point out that, while great benefits can be reached in general, advanced offloading strategies can be overly complex and even counter-productive. In contrast, simple augmentation at proxies to enable fragment caching and page composition achieves most of the benefit without compromising important considerations such as security.
ACM 1-58113-680-3/03/0005